Construction of Telephone Operable Message System - Hiran H. E. Jayaweera; Lelwala, R. (My University, 2007)
A password protected, dynam i c LCD (Liquid Crystal Display) m e ssaging board is developed to use with ordinary telephone is discussed in this publication. The device should be connected in parallel to a fixed- line telephone (called host telephone) and can be operated via host telephone itself or any other fixed-line or m obile telephone. After authentication, user can feed a m e ssage by using the built in standard m e ssage list or by typing each character via telephone keypa d. There are 9 standard m e ssages and a standard m e ssage can be extended up to 250 ch aracters and any of the ASCII characters can be used but only capital English letters, 0 to 9 and space are allowed when user feeding his own m e ssage through a telephone keypad.
Keywords: Construction of Telephone Operable Message System